2013
DOI: 10.1258/jtt.2012.120612
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of patients with hepatitis C in rural and remote Western Australia via telehealth

Abstract: Rural and remote patients at the Royal Perth Hospital were reviewed and treated for hepatitis C by a hepatologist and nurse practitioner using telehealth (videoconferencing). Over a four-year period, 50 patients were treated with pegylated interferon and ribavirin, and participated in a total of more than 500 telehealth sessions. Sustained virological response rates (SVRs) were compared to those in face-to-face (FTF) clinics to assess treatment outcomes. Treatment through telehealth was found to be non-inferio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 11 publications
2
60
0
Order By: Relevance
“…Of the 35 telehealth‐treated patients completing a satisfaction questionnaire, the majority reported that they were happy with the program and would participate again. This study suggested that telehealth is a feasible and effective option for treatment of patients with chronic HCV living in rural and remote areas, reducing the barriers to treatment …”
Section: Statewide Hcv Model Of Carementioning
confidence: 95%
See 2 more Smart Citations
“…Of the 35 telehealth‐treated patients completing a satisfaction questionnaire, the majority reported that they were happy with the program and would participate again. This study suggested that telehealth is a feasible and effective option for treatment of patients with chronic HCV living in rural and remote areas, reducing the barriers to treatment …”
Section: Statewide Hcv Model Of Carementioning
confidence: 95%
“…The success of telehealth in the management of patients with chronic HCV, who require frequent monitoring because of potentially severe side‐effects from treatment using IFN‐based therapies, have been well documented …”
Section: Statewide Hcv Model Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, the Infectious Diseases Society of America published a position statement supporting the use of evidence-based, cost-effective telehealth technologies for the treatment of infectious diseases 27. To assess treatment outcomes of patients in rural Western Australia with hepatitis C virus (HCV) infection treated using videoconferencing, investigators compared the sustained virologic response rate of patients treated using videoconferencing to that of patients treated in in-person clinics and found no significant difference 15. These results were similar to those of other studies conducted in underserved communities and in the custodial setting 28.…”
Section: Clinical Usementioning
confidence: 99%
“…The clinic aligns well with at least two of the Priority Actions identified in The Second Australian National Hepatitis B Strategy 2014-2017 (Australian Government Department of Health, 2014) and the NSW Hepatitis B Strategy 2014-2020 as well as recommendations of the Australian Hepatitis B Patient and Clinical Practice Survey (Hajarizadeh, Wallace, Ngo, & Richmond, 2014) and The Economic Cost and Health Burden of Liver Disease in Australia Report (Deloitte Access Economics, 2013). The nursing practice draws considerably from the successful Australian in rural settings (Nazareth et al, 2013) and in shared care arrangements experience of nurse models of hepatitis C care in a variety of settings, e.g. tertiary based liver clinics, prison settings, (Lloyd et al, 2013), in opioid substitution settings (Alavi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%